A STRUGGLE FOR LOVE OF BELLA SWAN REFLECTED IN NEW MOON MOVIE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Ayu Riska Lestari (University of Kuningan, 2012)
Abstract: This paper described the struggle for love of Bella Swan reﬂected in New Moon movie by using Alfred Adler’s individual psychology and analyzed the plot of the movie. It used qualitative research method and the object of this study was a major character named Bella Swan. Primary data sources were the New Moon movie directed by Christopher Weitz and the script of the movie, while secondary data sources were collected from many sources such as dictionary, articles from internet, and books related to this study. Methods of data collecting were observation and library research. The method of data analysis was descriptive analysis. Based on the analysis, It reﬂected the condition of a person who had a goal and struggle to get it. It concluded that Bella had high struggles to reach her goals. The plot of New Moon movie is complicated and stimulating, therefore it made the story was not ﬂat and boring. By analyzing the plot, the viewers could easily understand the story and the message of the movie and catchup the moral lesson of it.Keywords: Bella Swan, New Moon, Alfred Adler’s Individual Psychology, plot, struggle for love